2016
DOI: 10.1165/rcmb.2015-0228oc
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase Inhibition Attenuates Neonatal Hyperoxic Lung Injury and Enhances Nuclear Factor E2–Related Factor 2 Activation

Abstract: Oxygen toxicity and antioxidant deficiencies contribute to the development of bronchopulmonary dysplasia. Aurothioglucose (ATG) and auranofin potently inhibit thioredoxin reductase-1 (TrxR1), and TrxR1 disruption activates nuclear factor E2-related factor 2 (Nrf2), a regulator of endogenous antioxidant responses. We have shown previously that ATG safely and effectively prevents lung injury in adult murine models, likely via Nrf2-dependent mechanisms. The current studies tested the hypothesis that ATG would att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 51 publications
11
45
2
Order By: Relevance
“…Nrf2 activation in turn is able to overexpress, in these models, downstream expression of NQO1. Recently, the same research group obtained similar results in a model of newborn mice exposed to hyperoxia [71]. Indeed, they observed enhanced Nrf2 levels upon TrxR1 inhibition by a single dose of ATG.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samesupporting
confidence: 52%
See 1 more Smart Citation
“…Nrf2 activation in turn is able to overexpress, in these models, downstream expression of NQO1. Recently, the same research group obtained similar results in a model of newborn mice exposed to hyperoxia [71]. Indeed, they observed enhanced Nrf2 levels upon TrxR1 inhibition by a single dose of ATG.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samesupporting
confidence: 52%
“…Indeed, they observed enhanced Nrf2 levels upon TrxR1 inhibition by a single dose of ATG. Moreover, inhibition of TrxR1 in murine alveolar epithelial-12 cells by auranofin leads to Nrf2 overexpression with a consequent enhanced transcription of NQO1 and HO-1 [71].…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 98%
“…In addition, there was a significant induction of HO-1 at P3. Li et al demonstrated an induction of HO-1 after hyperoxic exposure for 3 days in newborn mice [55].…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental oxygen is an important aspect of treatment of premature neonates with respiratory failure. However, hyperoxic exposure triggers oxidative stress, results in lung injury and contributes to the development of BPD (3,4). Infants with BPD who were administered higher concentrations of supplemental oxygen were previously demonstrated to have more persistent lung disease (4).…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental oxygen is an important aspect of treatment of respiratory failure in premature neonates. However, oxidative stress induced by hyperoxic exposure results in overproduction of reactive oxygen metabolites (including hydrogen peroxide, singlet oxygen, superoxide free radicals, and hydroxyl free radicals), which overwhelms the immature antioxidant enzyme systems of premature neonates, causes lung injury, impairs alveolarization and leads to BPD (3,4).…”
Section: Introductionmentioning
confidence: 99%